Ion pair formation in the NeAr dimer irradiated by monochromatic soft X-rays - Ouchi, Takanari; Stumpf, Vasili; Miteva, Tsveta; Kuleff, Alexander I.; Gokhberg, Kirill (Chemical physics, 2016)
We investigated Ne+-Ar+ ion-pair formation which follows irradiation of the NeAr dimer by monochromatic soft X-rays. Using momentum-resolved electron-ion multicoincidence spectroscopy, we could unambiguously identify that the formation of the ion pair at photon energy of 200.5eV proceeds via interatomic Coulombic decay (ICD) of the Ne+(2s−1)Ar inner-valence ionized and NeAr+(3p−25d) ionization satellite states. Photoabsorption at higher photon energies of 268.2eV and 888.7eV leads to the emission of core electrons of Ar and Ne respectively, and to the subsequent local Auger decay process. We demonstrate that at these energies the ion pair formation originating in the doubly ionized Ar L-MM and Ne K-LL Auger final states proceeds mostly via radiative charge transfer and charge transfer driven by non-adiabatic coupling mechanisms.
Gesehen am 24.04.2018